2005
DOI: 10.1177/0146167205277092
|View full text |Cite
|
Sign up to set email alerts
|

How I See Me Depends on How I See We: The Role of Attachment Style in Social Comparison

Abstract: The self-concept is a social, flexible construct that shifts in response to the salience of a relationship partner. Three related experiments found that the tendency to pursue closeness in relationships (as measured by attachment style) served as a moderator of the shift. Specifically, individuals who avoid closeness in relationships became less similar to salient friends via contrast effects, whereas those who pursued closeness in relationships became more similar to salient friends via assimilation effects. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
28
0
1

Year Published

2008
2008
2021
2021

Publication Types

Select...
3
2
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 32 publications
(31 citation statements)
references
References 40 publications
2
28
0
1
Order By: Relevance
“…In addition, research by Gabriel, Carvallo, Dean, Tippin, Renaud (2005) has provided evidence that individuals with avoidant attachment styles scored lower than individuals with nonavoidant attachment styles on a measure of relational self-construal that was modified to relate to friendship (Footnote 1, Gabriel et al, 2005Gabriel et al, , p. 1571. As explained in previous studies (Milanov, Rubin & Paolini, 2012; press) our idea of communal identification is similar to the idea of relational self-construal applied in the area of ingroup identification.…”
Section: Hypothesesmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, research by Gabriel, Carvallo, Dean, Tippin, Renaud (2005) has provided evidence that individuals with avoidant attachment styles scored lower than individuals with nonavoidant attachment styles on a measure of relational self-construal that was modified to relate to friendship (Footnote 1, Gabriel et al, 2005Gabriel et al, , p. 1571. As explained in previous studies (Milanov, Rubin & Paolini, 2012; press) our idea of communal identification is similar to the idea of relational self-construal applied in the area of ingroup identification.…”
Section: Hypothesesmentioning
confidence: 99%
“…Different researchers have used categorical, continuous or both methods to measure attachment styles in their studies (Fraley & Waller, 1998;Gabriel et al, 2005;Mikulincer et al, 1998). The use of any of the two measurement methods usually depends on the specific topic of research and the phenomena that are being investigated.…”
Section: Hypothesesmentioning
confidence: 99%
“…These cognitive representations, called internal working models of attachment, regulate various aspects of information processing that guide thoughts, feelings, and behavior during relationship interactions (Collins & Read, 1990). Although originally conceptualized as a way to understand primary attachment processes with significant attachment figures (such as parents or romantic partners), research has shown that the attachment system can influence a multitude of outcomes seemingly unrelated to primary attachment, such as responses to needy strangers (Kestenbaum, Farber, & Sroufe, 1989), volunteerism intended to benefit strangers (Gillath et al, 2005), intergroup bias (Mikulincer & Shaver, 2001), and social comparison processes (Gabriel, Carvallo, Dean, Tippin, & Renaud, 2005;Mikulincer, Orbach, & Iavnieli, 1998). One of the central aspects of the attachment behavioral system is the avoidance dimension.…”
Section: Avoidance Of Intimacy and Social Comparisonmentioning
confidence: 99%
“…Only non-avoidant individuals assimilate the characteristics of primed friends; avoidant individuals view themselves as less similar to primed friends (Gabriel et al, 2005). Thus, one might predict that avoidant individuals would benefit from friends who are viewed as uniformly negative.…”
Section: Avoidance Of Intimacy Friendship and Self-likingmentioning
confidence: 99%
“…Self-concept contains both beliefs and evaluations of the self (Campbell, Assanand, & Di Paula, 2003) and is developed through our social interactions (Kanagawa, Cross, & Markus, 2001;Tarrant, MacKenzie, & Hewitt, 2006). The self-concept is flexible (Gabriel et al, 2005) but overall psychological well-being has been linked to the existence of a core self that is consistent across roles (Donahue et al, 1993). The women in this work identified feeling as Community and Belonging 56 though they lacked a solid sense of themselves as their survival strategies involved taking on multiple roles and identities.…”
Section: Community and Belonging 55mentioning
confidence: 92%